Rethinking human resources and capacity building needs for malaria control and elimination in Africa. - Halima Mwenesi; Charles Mbogo; Núria Casamitjana; Marcia C Castro; Maurice A Itoe; Friday Okonofua; Marcel Tanner (Public Library of Science (PLoS), 2022)
Despite considerable success in controlling malaria worldwide, progress toward achieving malaria elimination has largely stalled. In particular, strategies to overcome roadblocks in malaria control and elimination in Africa are critical to achieving worldwide malaria elimination goals-this continent carries 94% of the global malaria case burden. To identify key areas for targeted efforts, we combined a comprehensive review of current literature with direct feedback gathered from frontline malaria workers, leaders, and scholars from Africa. Our analysis identified deficiencies in human resources, training, and capacity building at all levels, from research and development to community involvement. Addressing these needs will require active and coordinated engagement of stakeholders as well as implementation of effective strategies, with malaria-endemic countries owning the relevant processes. This paper reports those valuable identified needs and their concomitant opportunities to accelerate progress toward the goals of the World Health Organization's Global Technical Strategy for Malaria 2016-2030. Ultimately, we underscore the critical need to re-think current approaches and expand concerted efforts toward increasing relevant human resources for health and capacity building at all levels if we are to develop the relevant competencies necessary to maintain current gains while accelerating momentum toward malaria control and elimination.